Pengaruh Psychological Well-Being terhadap Loneliness pada Mahasiswa Semester 2 FKIK Universitas Jambi - Nadia Dwi Amanda; Fenny Dhea Arfani; Ulfa Magfiroh; Beny Rahim; Jelpa Perianto; Dinda Agraiza; Muhammad Ilham (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Psychological well-being describes a person's psychological success and capacity to accept himself, be able to socialize be able to control himself. Meanwhile, loneliness is a mental condition characterized by feelings of emptiness. The purpose of the study was to determine the level of psychological well-being relationship with loneliness using the quantitative method of the correlational method. This study uses a non-probability sampling technique with a purposive sampling method consisting of 70 Semester 2 Students of the Faculty of Medicine and Health Sciences, University of Jambi. According to Ryfff's Scales of Psychological Well-Being and the Loneliness Scale, with the technical analysis of descriptive statistical program Jeffreys's Amazing Statistics Program versi 0.96.0. The results of the hypothesis test through correlation analysis showed a significant value with the direction of the negative relationship (inversely proportional) between psychological well-being and loneliness (r = -0.298; p = 0.012 < 0.05). This study indicates that the higher the psychological well-being of students, the lower the level of loneliness felt. On the other hand, low psychological well-being due to academic burden and lack of social support can increase feelings of isolation, so it is necessary to strengthen psychological aspects and adequate social support for early year students.